PENGARUH TRANSAKSI NON TUNAI TERHADAP VELOCITY OF MONEY DI INDONESIA TAHUN 2011-2021 - , Anthony Mayes, Tamia Yolanda , Any Widayatsari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study intend to determine the effect of electronic money transactions and debit card transactions on the velocity of money in Indonesia. The data used in this study is annual data from 2011-2021. The method used is quantitative with data analysis, a multiple linear regression analysis model using the OLS (Ordinary Least Square) approach using Eviews 12. The results of this study show that electronic money transactions and debit card transactions simultaneously affect money circulation. Partially, electronic money transactions do not have a significant effect on velocity of money in Indonesia and debit card transactions have a negative significant effect on velocity of money in Indonesia.  Keyword: Electronic Money, Debit Card, velocity of money